Konsep Ihtiyāṭ Imam Syafi’i terhadap Anjuran Menutup Aurat bagi Anak-Anak; Analisis Tindakan Preventif Pelecehan Anak - Arsyad, Azman; Ibtisam, Ibtisam; Asti, Mulham Jaki (Universitas Islam Negeri Alauddin Makassar, 2020)
The basic principle in Islamic law is to provide mashlahah to mankind, so that the main objective of a law requirement must be based on the maqashid sharia aspect, namely realizing benefits for humans both in world affairs and in the afterlife. Children as part of the foundation of religion because in the future they will become the successors of the ummah, Islam is here to provide protection for them, both maintaining their survival, proper education. Preventive measures must be taken to avoid bad behavior. The purpose of this study was to explore and refer to the concept of ihtiyat Imam Syafi'i regarding the suggestion of covering one's genitals with children. The research method used is library research and is qualitative in nature. Sources of data used in this study come from primary and secondary data. The result of this research is that the ability to cover the genitals of children is a form of precaution to avoid unwanted things